PERWALIAN TERHADAP CUCU BERUSIA DI ATAS 18 TAHUN DI TAKALAR SULAWESI SELATAN: Guardianship For His Above 18 Years Old Grandchild In Takalar, South Sulawesi - Fadhillah Balqis Dasril; Setyaningsih (Faculty of Law, Universitas Trisakti, 2024)
An unhappy marriage can lead to guardianship of children. The formulation of the problem Can a grandchild over the age of 18 be asked for guardianship according to the Marriage Law and the KHI? And is the judge's decision in accordance with the Marriage Law and the KHI? The research was carried out normatively, the descriptive nature of the analysis, sourced from secondary data, analyzed causatively and drew conclusions with deductive logic. The result is guardianship under the Marriage Law and KHI, there are significant differences. Where in the Marriage Law, guardianship applies if the age of the child is under 18 years old or unmarried or not under the power of his parents. The conclusion is that the pleading for the guardianship regarding the grandchild whose age above 18 years old using the Article 50 Number 1 of Marriage law is not precisely applied 2) The verdict that have been ruled out by the judge is not accordance with Article 50 Number 1 of Marriage Law.